Proceedings of the 2nd Czech-China Scientific Conference 2016 - Petr Praus; Jaromir Gottvald (IntechOpen, 2017)
This book comprises the proceedings of the 2nd Czech-China Scientific Conference 2016 which was held on 7th June 2016 in Ostrava, Czech Republic. The objective of the conference was to present the latest achievements in the fields of advanced science and technology that stem from research activities of V
English
Keywords: Engineering; Physical Sciences; Engineering and Technology; Structural Engineering; Civil Engineering